STRATEGI KOMUNIKASI PRAMUWISATA DALAM MEMPROMOSIKAN PARIWISATA KOTA MAKASSAR - Windra Aini; Hijrah Hijrah; Suardi Suardi (Universitas Merdeka Malang, 2020)
This study aims to describe the communication strategies carried out by tour guides in promoting tourism of Makassar City. The communication made by tour guides has a strategic role in building a good impression with tourists. The good impression that tourists get can be an effective means of promotion when tourists share their experiences with others. The approach used in this research is a qualitative descriptive method with interviews as a data collection technique. There are 7 informants, all of whom are tour guides in Makassar city. The results showed that the Makassar city tour guide provided information using good communication, provided the best service and was able to understand the characteristics of tourists well.